Tutors’ Perspectives of Advancing Distance Learning Programs: A Comprehensive Understanding - Islam, Mohammad Rezaul; Mahmud, Nazim (International Review of Research in Open and Distributed Learning, 2025)
This study critically examined tutors’ perspectives on advancing the academic development of teacher education programs delivered via open and distance learning (ODL) at Bangladesh Open University (BOU). Tutors play a pivotal role as frontline facilitators of instruction, yet their experiential insights are often underrepresented in institutional decision-making. Drawing on a constructivist paradigm and grounded theory methodology, this qualitative inquiry engaged 82 tutors across eight tutorial centres using open-ended survey questions. Through classical content analysis, eleven major themes emerged, including attendance in tutorial sessions, curriculum and module design, tutorial session frequency, physical resources, tutor professional development, and supervision of practice teaching. The findings reveal that tutors emphasise the need for structured learner engagement, participatory curriculum revision, robust infrastructural support, and institutional investment in tutor capacity-building. The study also highlights disparities between current program structures at BOU and international norms, suggesting the need for extended program duration and more integrated practicum experiences. Implications are drawn for institutional policy, academic design, and participatory governance in ODL. By foregrounding tutors’ voices, this study contributes to a more inclusive model of academic development and underscores what tutors perceive as the need to bridge the gap between policy directives and pedagogical realities in distance education.